Mineralogy of dumortierite-bearing abyssal pegmatites at Starkoc and Bestvina, Kutna Hora Crystalline Complex - Cempirek,J.; Novak,M. (Journal of the Czech Geological Society, 2006)
Abyssal pegmatites from Starkoc and Bestvina are typical examples of the AB-BBe subclass pegmatites in the Bohemian Massif. The features typical for origin and evolution of both abyssal pegmatites are better preserved in the pegmatite at Starkoc, where, based on paragenetic relationships, three distinct assemblages were recognized: (i) Primary igneous assemblage: plagioclase I + quartz I + muscovite + garnet III + tourmaline I + dumortierite I + chrysoberyl; (ii) Prograde metamorphic assemblage: quartz II + plagioclase II + kyanite + K-feldspar + staurolite + tourmaline II + dumortierite II; (iii) Retrograde metamorphic assemblage: pyrophyllite and kaolinite. Plagioclase, quartz and muscovite are major minerals in the pegmatite veinlet; the most common accessory minerals include tourmaline, dumortierite, garnet, K-feldspar and kyanite, whereas only trace amounts of chrysoberyl, staurolite and several very rare accessory minerals were found. Composition of tourmaline is controlled by the two-stage evolution of the pegmatite. Primary tourmaline I from Starkoc exhibits crystallization trend expressed by the substitution (Y,ZAlTAl)(Y,ZR2+TSi4+)-1. Prograde metamorphic event introduced additional Fe and Mg from the host rock into the system and remobilization of B allowed crystallization of Mg-enriched, rather homogeneous tourmaline II. Starkoc and all other known pegmatites of AB-BBe subclass in the Bohemian Massif occur in the Gfohl Unit, along the easternmost border of the Moldanubicum. Pegmatite host rocks exhibit HP metamorphic conditions and low degree of MP overprint. Such metamorphic evolution is a typical feature of host rocks of similar abyssal pegmatites in high-grade terrains in Antarctica, Norway and Madagascar.
Keywords: Abyssal pegmatite; dumortierite; tourmaline; Kutna Hora Crystalline Complex